PERBEDAAN KEJADIAN DEPRESI PADA PRIA DAN WANITA PADA LANSIA YANG MENDERITA DIABETES MELLITUS: The Diferences of Depression in Man and Women Elderly who Have Diabetes Mellitus - Nur Ainiyah; Iis Noventi; Chilyatiz Zahroh (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2021)
Elderly is the final stage of the human life cycle. The process of aging is a process that shows a decline in human physical function, emotional changes, as well as social interactions that will change gradually. Diabetes Mellitus (DM) is a metabolic disease that occurs chronically due to interference with insulin and has various complications for sufferers, both acute and chronic. Decreased physical, unstable emotional, interaction of social abilities decrease, anda also metabolic disorders and its complications make the elderly had depression which is manifested in the quality of sleep of the elderly. The purpose of this study was to determine the differences in the incidence of depression in men and women in the elderly who suffer from diabetes mellitus. The method in this research was comparative. The population of this study were all elderly in Region X as many as 60 elderly consisting of 27 elderly men and 33 elderly women. The sample in this study was a research of 60 members, using total sampling / depression data collection was done by giving a questionnaire based on the Beck depression scale. Data analysis used elderly depression scores in men and elderly women collected from the results of data collection will be measured the difference with a two-mean difference test (T-test). The results showed the mean depression score for men = 1.59 and the standard deviation = 1.575 and the mean depression score for women = 3.54 the standard deviation was 1.96, the level of significance (p = 0.001; p <0.05). Its shows a significant difference between depression in elderly men and women who suffer from DM. Therefore, it is expected that all members of the elderly family as one of the support systems for the elderly can provide support so that the elderly do not experience depression.